2023
DOI: 10.4085/1062-6050-0375.21
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Identifies First Rib Stress Fractures: A Case Series in National Collegiate Athletic Association Division I Athletes

Abstract: Isolated first rib stress fractures in athletes are thought to be rare. In this case series, three Division I athletes developed isolated first rib stress fractures over the span of one year, revealing that these may occur more often than previously understood. These fractures can be easily missed because of low incidence, lack of clinical suspicion, and vague presentation. Further, radiographs can fail to reveal such fractures. To our knowledge, this is the largest case series of athletes with first rib stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Some studies have shown that depression remarkably affects the cognitive ability of many elderly patients with fracture complicated with cerebrovascular accident. [33][34][35] Foreign scholars have found that depression often experienced by elderly patients with fracture complicated with cerebrovascular accident will affect cognitive ability, and insecurity will coexist with depression. A high level of insecurity will also affect the ability of cognitive adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that depression remarkably affects the cognitive ability of many elderly patients with fracture complicated with cerebrovascular accident. [33][34][35] Foreign scholars have found that depression often experienced by elderly patients with fracture complicated with cerebrovascular accident will affect cognitive ability, and insecurity will coexist with depression. A high level of insecurity will also affect the ability of cognitive adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…As point-of-care ultrasound becomes more readily accessible, there is one case series that referenced the potential use of ultrasound as a screening modality for first rib stress injuries and fractures, but more research needs to be done on its effectiveness (18).…”
Section: Discussionmentioning
confidence: 99%